2021
DOI: 10.3390/ijms22115855
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Alterations in Glioblastoma (GBM)

Abstract: Glioblastoma (GBM) is an extremely aggressive tumor originating from neural stem cells of the central nervous system, which has high histopathological and genomic diversity. Mitochondria are cellular organelles associated with the regulation of cellular metabolism, redox signaling, energy generation, regulation of cell proliferation, and apoptosis. Accumulation of mutations in mitochondrial DNA (mtDNA) leads to mitochondrial dysfunction that plays an important role in GBM pathogenesis, favoring abnormal energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…On the contrary, TMZ treatment was shown to stimulate mitochondrial respiration. Since the measurement of oxygen consumption was normalized to the number of viable cells, this activity could be attributed to its ability to increase the number of mitochondria per cell 45,46 . Nevertheless, the combination treatment in U87 GBM cells seems to make mitochondria more active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, TMZ treatment was shown to stimulate mitochondrial respiration. Since the measurement of oxygen consumption was normalized to the number of viable cells, this activity could be attributed to its ability to increase the number of mitochondria per cell 45,46 . Nevertheless, the combination treatment in U87 GBM cells seems to make mitochondria more active.…”
Section: Discussionmentioning
confidence: 99%
“…Since the measurement of oxygen consumption was normalized to the number of viable cells, this activity could be attributed to its ability to increase the number of mitochondria per cell. 45 , 46 Nevertheless, the combination treatment in U87 GBM cells seems to make mitochondria more active. Bearing in mind that U87 cells rely primarily on glycolysis rather than OxPhos, 47 we could speculate that TMZ in the presence of DIA induced a shift in metabolic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some GSCs contain higher levels of ATP than differentiated GBM cells, complicating the overall picture of metabolic reprogramming and illustrating intratumoral heterogeneity at the metabolic level, while suggesting that purely targeting the glycolytic pathway may not be effective against all GSCs [ 66 , 67 ]. In fact, mutations are found throughout the mitochondrial DNA genome in GBM cells, altering metabolic pathways and energy generation and contributing to therapeutic resistance [ 68 ]. Certain GSC subtypes rely on the glycolytic pathway to greater extents than other subtypes, which also utilize the mitochondrial pathways, illustrating the need for multiple therapeutic targets [ 63 , 67 ].…”
Section: Interactions With Tumor Microenvironmentmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that mitochondria play an important role in gliomas, including GBM. Mitochondrial DNA (mtDNA) alterations are associated with cellular and metabolic consequences, diagnosis, prognosis, and treatment of GBM [11]. Mitochondrial dynamics are reportedly essential for the development of gliomas.…”
Section: Introductionmentioning
confidence: 99%